P, S Ligands for the Asymmetric Construction of Quaternary Stereocenters in Palladium‐Catalyzed Decarboxylative [4+2] Cycloadditions. (6th January 2016) - Wei, Yi; Lu, Liang‐Qiu; Li, Tian‐Ren; Feng, Bin; Wang, Qiang; Xiao, Wen‐Jing; Alper, Howard
Abstract: A new hybrid P, S ligand was exploited by combining a chiral β‐amino sulfide and a simple diphenyl phosphite. The resultant ligand performs extremely well in a palladium‐catalyzed asymmetric decarboxylative [4+2] cycloaddition reaction, thus generating multiple contiguous stereocenters and a chiral quaternary center. By doing so, a straightforward route to highly functionalized tetrahydroquinolines was developed with yields of up to 99 %, as well as 98 % ee and greater than 95:5 d.r. Moreover, mechanistic insights into this transformation and the possible stereocontrol are discussed.